PERBANDINGAN CERAMAH DAN SIMULASI MONOPOLI TENTANG MENSTRUASI TERHADAP PENGETAHUAN DAN SIKAP SISWI - Sylvianovelista Losoiyo (Pasapua Health Journal, 2019)
Introduction : In adolescence, having poor knowledge about reproductive health will have a negative impact on their attitudes and behavior in acting so that knowledge about menstruation needs to be owned early on. This study aims to find out the comparison of lectures and monopoly simulations of menstruation on female students’ knowledge and attitudes. Method: Quasi experimental with nonequivalent control group design. Sampling was done by purposive sampling technique with the number of samples in this study 78 students and divided into 3 groups. Data were analyzed using the Mann-Whitney test. Result : Pre lecture Knowledge Test obtained p value = 0.73 and then after the post test was obtained p value = 0.00 <α = 0.05. Then for the pre test attitudes to get results p value = 0.76 and after the post test get the results p value = 0.00 <α = 0.0 and the Simulation method is obtained for pre Knowledge Test with p value = 0.59. Then after the post test is obtained the result is p value = 0.00 <α = 0.05. Then the attitude to get results p value = 0.76. after the post test the results obtained p value = 0.00 <α = 0.05. Conclusion : There is a difference between the lecture method and the monopoly simulation of knowledge and student attitudes.